Ganti Rugi Pengadaan Tanah untuk Pembangunan Bandar Udara dalam Perspektif Hukum - Elis Rusnita; Frency Siska (UPT Publikasi Ilmiah Unisba, 2025)
Abstract. The land acquisition process for Tongkonan customary land in Tana Toraja reveals a gap between the individualistic nature of national law, as reflected in Law No. 2 of 2012, and the communal nature of customary law, particularly regarding compensation mechanisms that fail to accommodate local customary values. Collective ownership, which cannot be individually certified, creates complexity in determining rightful parties and compensation distribution. This research aims to provide a deeper understanding of the need for legal protection of indigenous peoples' rights to their customary land and to formulate a compensation mechanism aligned with local cultural values. The research employs a juridical-empirical approach, with a descriptive-analytical type of legal research, using primary and secondary data, primary, secondary, and tertiary legal materials, and data collection techniques through literature study, interviews with customary leaders, and data triangulation. The conclusion highlights the urgency of integrating national and customary legal systems in land acquisition processes to ensure substantive justice for the Toraja indigenous community. Abstrak. Pengadaan tanah adat Tongkonan di kabupaten Tana Toraja memperlihatkan ketidaksesuaian antara norma hukum nasional yang individualistik dalam UU No. 2 Tahun 2012 dengan sistem hukum adat yang komunalistik, khususnya terkait mekanisme ganti rugi yang belum mengakomodasi nilai-nilai adat. Kompleksitas muncul dari kepemilikan kolektif yang tidak dapat disertifikatkan secara individual, sehingga menimbulkan tantangan dalam penentuan subjek hak dan pembagian kompensasi. Penelitian ini bertujuan memberikan pemahaman atas pentingnya perlindungan hukum hak masyarakat adat atas tanah ulayat, serta merumuskan mekanisme ganti rugi yang sesuai nilai budaya setempat. Metode yang digunakan adalah pendekatan yuridis empiris dengan jenis penelitian hukum deskriptif analitis, menggunakan data primer dan sekunder, bahan hukum primer, sekunder, dan tersier, serta teknik pengumpulan data melalui studi pustaka, wawancara tokoh adat, dan triangulasi data. Simpulan menunjukkan perlunya integrasi hukum nasional dan hukum adat dalam pengadaan tanah untuk menjamin keadilan substantif bagi masyarakat adat Toraja.